(3Х + 2)*( 3X - 4 ) = 9X^2 - 12X + 6X - 8 = 9X^2 - 6X - 8
=========================================
( 2X + 3)*( 3X - 1 ) = 6X^2 - 2X + 9X - 3 = 6X^2 + 7X - 3
=========================================
( 3X + 1)*( X - 4 ) = 3X^2 - 12X + X - 4 = 3X^2 - 11X - 4
==========================================
6X^2 + 7X - 3 + 3X^2 - 11X - 4 = 9X^2 - 4X - 7
===========================================
9X^2 - 6X - 8 = 9X^2 - 4X - 7
9X^2 - 9X^2 - 6X + 4X - 8 + 7 = 0
- 2X - 1 = 0
2X = - 1
X = ( - 0.5 )
===========================================
Ответ Х = ( - 0.5 )